C-11 methionine positron emission tomography scans improve the preoperative localization of pathologic parathyroid glands in primary hyperparathyroidism. (February 2022) - Iversen, Peter; Arveschoug, Anne K.; Rejnmark, Lars; Rolighed, Lars
Background and objective: Preoperative localization of pathologic parathyroid glands is essential in the preparation of a parathyroidectomy. We evaluated the use of a C-11 methionine positron emission tomography/computed tomography scan in a 7-year period in selected patients with primary hyperparathyroidism. The indications to perform a C-11 methionine positron emission tomography/computed tomography were either persistent primary hyperparathyroidism after parathyroidectomy or inconclusive preoperative localization on ultrasound and sestaMIBI. Methods: A group of 36 patients was referred for a C-11 methionine positron emission tomography/computed tomography. Biochemical data, pathology, and results of sestaMIBI were collected retrospectively. The primary hyperparathyroidism patients were divided into two groups. In group 1 ( N = 17), the C-11 methionine positron emission tomography/computed tomography was performed before parathyroidectomy. In group 2 ( N = 19), the C-11 methionine positron emission tomography/computed tomography was performed after unsuccessful parathyroidectomy and before a reoperation. Results: Overall, in 30 of the 36 patients (83%), C-11 methionine positron emission tomography/computed tomography identified a true-positive pathologic parathyroid gland confirmed by an experienced pathologist, consistent with a positive predictive value of 91%. In group 1, 94% of the patients ( N = 16) had pathologic parathyroid tissue identified by C-11 methionine positron emission tomography/computed tomography. This resulted in a clinical benefit in 13 patients (76%). In group 2, the benefit was slightly lower, as 74% of the patients ( N = 14) had a true-positive C-11 methionine positron emission tomography/computed tomography scan resulting in a clinical benefit in nine patients (47%). Conclusions: In two selected groups of patients planned for an initial operation or reoperation of primary hyperparathyroidism and inconclusive conventional imaging, we found C-11 methionine positron emission tomography/computed tomography to give parathyroid surgeons a clinical benefit in the majority of cases, electing the patients for unilateral surgery.